La concesión forestal: de instrumento jurídico en el olvido a herramienta esencial para el manejo forestal comunitario - Amaya-Arias, Angela María (Universidad Nacional del Litoral, 2020)
The concession is a legal tool that is in force in the Colombian legal system. However, it is currently not regulated and has not been used for more than 20 years for forest use. This article aims to analyze the case of Guatemala, in which the forest concession is a fundamental figure for the development of community forestry, to finally provide inputs for the regulation of this tool in Colombia, and thus promote community forest management in the country.